Alternatif Model Alat Evaluasi Kemahiran Menyimak Bahasa Indonesia bagi Penutur Asing Berlandaskan Alat Evaluasi Bahasa Asing - Ida Widia (Badan Pengembangan dan Pembinaan Bahasa, 2021)
In this paper, we will discuss the design of the Indonesian language evaluation model for foreign speakers (BIPA), in particular the listening proficiency evaluation model. Listening proficiency evaluation tool is considered important because listening is a parameter for a foreign speaker to master other language skills. At this time, the presentation of the listening proficiency test for the Indonesian language proficiency test (UKBI) is considered difficult for foreign speakers to follow. The solution to overcome this problem is to design a listening proficiency evaluation tool based on the results of analysis of foreign language evaluation tools such as the JLPT (Japanese Language Proficiency Test), America by analyzing the listening competency evaluation tool from TOIEC (Test of English for International Communication), and Europe with analyzing the DELF listening competency evaluation tool (Diplôme d'Etudes en Langue Française / Diploma in French Language Studies). The results of the study on the evaluation tool became an alternative basis for designing a model for evaluating listening proficiency in Indonesian for foreign speakers. This study aims to describe the design of the listening evaluation tool in Indonesian for foreign speakers. The data that will be produced in this research is in the form of an alternative lattice evaluation tool for listening proficiency in Indonesian for foreign speakers.